Absceded abdominal wall desmoid tumor: a case report - Mena Zenteno, Ana Karen; Olvera, Aldo; Sánchez, Cynthia; Montero, Jorge A. (International Journal of Research in Medical Sciences, 2023)
Desmoid tumor is a rare type of tumor dependent on a well-differentiated fibroblastic monoclonal proliferation with a high capacity for non-metastatic local invasion, it constitutes <3% of soft tissue neoplasms, an annual incidence of 5-6 cases per million is reported, its etiology is unknown and its clinical presentation depends on the location of the tumor. We presented a case of a 53-year-old female patient who presented to the emergency department with clinical characteristics of abdominal wall abscess with no significant history of its appearance. Abscess drainage plus biopsy of muscle tissue in the anterior region of the abdominal wall was performed, histopathology report compatible with desmoid tumor, radical surgical treatment was decided in a second intervention. Desmoid tumor is rare, since its diagnosis and treatment require a multidisciplinary approach; Active surveillance is currently the treatment of choice for patients who have DD in noncritical locations, and at least 1 to 2 years of active surveillance is now recommended because of its likelihood of spontaneous regression. The main objective of all existing therapies is to preserve or improve the quality of life of the patient.